1993
DOI: 10.2514/3.11314
|View full text |Cite
|
Sign up to set email alerts
|

Near-wall variable-Prandtl-number turbulence model for compressible flows

Abstract: A near-wall variable-Prandtl-number turbulence model is developed for the calculations of high-speed compressible turbulent boundary layers. The model is based on the k-e and the 0 2 -e Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 22 publications
3
13
0
1
Order By: Relevance
“…A variable Pr T model proposed by Xiao et al (2007) is found to improve SBLI results. Similar models are proposed by Sommer, So & Zhang (1993), Brinckman, Calhoon & Dash (2007) and Goldberg et al (2010). In another work, Bowersox (2009) presents the exact transport equation for the turbulent energy flux, and simplifies it to get an algebraic model in terms of gradients in mean quantities.…”
Section: Introductionmentioning
confidence: 89%
“…A variable Pr T model proposed by Xiao et al (2007) is found to improve SBLI results. Similar models are proposed by Sommer, So & Zhang (1993), Brinckman, Calhoon & Dash (2007) and Goldberg et al (2010). In another work, Bowersox (2009) presents the exact transport equation for the turbulent energy flux, and simplifies it to get an algebraic model in terms of gradients in mean quantities.…”
Section: Introductionmentioning
confidence: 89%
“…Variable P r t models have had difficulty matching experimental data. [11][12][13][14] Scale resolving simulations (SRS) have become a major focus in recent years. Detached Eddy Simulation (DES) and Large Eddy Simulation (LES) allow the largest scales of turbulence to be resolved while filtering (implicitly or explicitly) the smallest scales.…”
Section: B Numerical Backgroundmentioning
confidence: 99%
“…For the considered flow, the thermal boundary layer is greatly modified by the heat source such that the use of this similarity is questionable. One can compute a variable turbulent Prandtl number by solving two extra transport equations [64,6] namely one for the variance of the temperature fluctuation and the other for its dissipation rate. Such a model was partly implemented in GASP, but was not completed due to time constraints.…”
Section: Discussionmentioning
confidence: 99%